Bridging the Gap between Nonliving Matter and Cellular Life (Small 13/2023). Issue 13 (29th March 2023) - Kumar, Sumit; Karmacharya, Mamata; Cho, Yoon‐Kyoung
Abstract : Artificial Cells In article number 2202962, Yoon‐Kyoung Cho and co‐workers discuss the latest advances in cell membrane‐engineered micro or nanoreactors that simulate biochemical compartments, signaling cascades, energy generation, growth, reproduction, and adaptability. These reactors have the potential to provide hybrid solutions for pharmaceutical drugs, biosensors, novel materials, and biochemical microreactors.